Thermal Properties of Polyester/Epoxy Blend - Ali, Aqeel Mohsin; Jaber, Mohammed A.; Toama, Nooraldeen A. (Iraqi Journal of Science, 2021)
Unsaturated polyester toughened Epoxy was developed. Epoxy resin had toughened by weight fraction of 10, 20, 30, and 40 wt. % unsaturated polyester. FTIR spectroscopy has been used to investigating the intermolecular hydrogen bonding. Unsaturated polyester–epoxy matrices were characterized for their thermal properties. The FTIR test detected a peak shift of the functional groups which can explain cross-linking occurs between the two resins. The crosslinking between epoxy and unsaturated polyester confirmed via the existence of the stretching asymmetrical C-C band and contraction of the C-O band. The DSC test demonstrated that glass transition temperature value decreases with epoxy strengthening. The specific heat capacity and thermal conductivity have been affected the unsaturated polyester percentage. Thermal conductivity, specific heat capacity and thermal effuisivity increased by weight fraction of polyester. The thermal diffusivity values of blends showed a little decreasing.